The Regulation of Electronic Transaction in Indonesia - ZAMRONI, Mohammad; PUTERA, Andika Persada (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018DO - 10.14505//jarle.v9.7(37).35, 2019)
The development of electronic transaction rises a positive atmosphere for the economy growth. Similar to such a transformation, however, this kind of transaction also brings negative effects with it as well. Any deception and deceitfulness in electronic transaction are often found, while the injured parties feel doubt to do legal actions on it. Basically, the regime of cyber law in Indonesia has anticipated the negative effects of electronic transaction by enacting a series of regulations on that issue. As like another regulation, however, those regulations remain unclear. The actors of the transaction, particularly the consumers, have not completely understood the characteristics of electronic transaction, and thus, it makes them injured. Therefore, this study aims to analyze the characteristics of electronic transaction in Indonesia Regulation.